Učinek glasbe - Stefanija, Leon (Muzikološki zbornik, 2007)
The essay offers a survey of research into musical effects. The text is centred in the question regarding the epistemological range in the research into music's effects. They are discussed through the context of studies on music' functions and music preferences.
Keywords: funkcije glasbe; muzikologija; socialna psihologija glasbe; spoznavoslovje glasbe; učinki glasbe